Frost resistance of seeds in Mediterranean oaks and the role of litter - Esteso-Martínez, Jordán; Gil-Pelegrín, Eustaquio (Ann. For. Sci., 2004)
The endogenous frost resistance of the seeds of four Mediterranean oaks (Quercus coccifera, Q. faginea, Q. ilex and Q. pyrenaica) with different leaf abscission phenology was tested. Thermal analysis and polyelectrolytes leakage methodologies were employed to establish lethal temperature thresholds. Results showed a higher frost resistance for evergreen species and lower for deciduous species in this decreasing order: Q. coccifera, Q. ilex, Q. faginea and Q. pyrenaica. The cover of leaf litter generated by deciduous species could be an isolating element which allowed seed survival under cold winter conditions to that species with a lower frost resistance. Differences in temperature above and below a leaf litter cover along a winter season were measured in a Q. faginea stand, in this sense the kind effect of leaf litter from a thermal point of view was proved.
Keywords: frost resistance; leaf litter; polyelectrolytic leakage; Quercus; thermal analysis

Long-term CO 2-enrichment in a Mediterranean natural forest: An application of large Open Top Chambers - Angelis, P. De; Scarascia-Mugnozza, G. E. (Chemosphere, 1998)
It is crucial to be able to anticipate the possible effects of environmental changes on the Mediterranean woodland communities given their essential role on protecting lands that are under a strong pressure by man and climate. Predictions of the effects of increasing C0~ concentration on plants have been inferred by short- and long-term studies, conducted at different scales and by different technologies. Open Top Chambers (OTCs) are experimental facilities that have been widely used to expose field grown plants to different pollutant gases, and more recently to elevated [CO2] . In this paper, we present the natural site and the experimental system (six large OTCs enclosing clumps of natural vegetation) that we have been utilizing for 3 years, to assess the impact of elevated [CO2] on a Mediterranean natural forest community. The results show that large OTCs can be usefully used to simulate C02 doubling even under the harsh environmental conditions of the mediteffanean region
Keywords: decomposition; Elevated CO3; leaf litter; Mediterranean forest (voyant)

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L. V.; Olivares-Bernabeu, C. (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia